A qualitative study to inform adaptations to a brain health intervention for older adults with type 2 diabetes living in rural regions of Ireland. Issue 4 (10th January 2023) - McEvoy, Claire T.; Regan‐Moriarty, Joanne; Dolan, Catherine; Bradshaw, Caroline; Mortland, Valerie; McCallion, Maire; McCarthy, Geraldine; Kennelly, Seán P.; Kelly, Jim; Heffernan, Margaret; Kee, Frank; McGuinness, Bernadette; et al.
Abstract: Aims: Type 2 diabetes is a risk factor for late‐life dementia, but dementia prevention strategies have yet to be comprehensively evaluated in people with diabetes. The Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) demonstrated cognitive benefits of a 2‐year multidomain lifestyle intervention. However, given the intensive nature of FINGER, there is uncertainty about whether it can be implemented in other high‐risk populations. Our aim was to explore attitudes towards dementia risk, and barriers to an intervention based on the FINGER model in older adults with type 2 diabetes living in rural areas of Ireland. Methods: Focus groups were conducted with 21 adults (11 men and 10 women) aged 60+ years with type 2 diabetes living in border regions of north and south Ireland. Data were analysed using thematic analysis. Results: There was limited understanding of diabetes as a risk factor for late‐life dementia. The main barriers to engagement with the multidomain intervention were eating foods that were not compatible with cultural norms, time and travel constraints, and perceived lack of self‐efficacy and self‐motivation for adopting the desired diet, exercise and computerised cognitive training (CCT) behaviours. Facilitators for intervention acceptability included the provision of culturally tailored and personalised education, support from a trusted source, and inclusion of goal setting and self‐monitoring behavioural strategies. Conclusions: While there was high acceptability for a brain health intervention, several barriers including cultural food norms and low self‐efficacy for adopting the diet, exercise and CCT components would need to be considered in the intervention design. Findings from this study will be used to inform local decisions regarding the adaptation of FINGER for people with type 2 diabetes. The feasibility of the adapted multidomain intervention will then be evaluated in a future pilot trial.